Mesenchymal Stem Cell-Derived Exosomes and Their Potential Agents in Hematological Diseases. (28th September 2021) - Shen, Min; Chen, Tong
Abstract : Mesenchymal stem cells (MSCs) are the most exploited stem cells with multilineage differentiation potential and immunomodulatory properties. Numerous lines of findings have reported their successful applications in a multitude of inflammatory conditions and immune disorders. However, it is currently discovered that these effects are mainly mediated in a paracrine manner by MSC-exosomes. Moreover, MSC-exosomes have been implicated in a wide variety of biological responses including immunomodulation, oxidative stress, tumor progression, and tissue regeneration. Meanwhile, they are reported to actively participate in various hematological diseases by the means of transferring different types of exosomal components to the target cells. Therefore, in this review, we briefly discuss the sources and biological features of MSCs and then illustrate the biogenesis and biological processes of MSC-exosomes. Of note, this paper especially highlights the latest research progress of MSC-exosomes in hematological diseases.